Handbook: Rural extension, Volume 2: Examples and background material - Hoffmann, Volker; Christinck, Anja; Lemma, Mamusha (CTA / GTZ / Margraf / Universität Hohenheim, 2009)
Agricultural extension services in many developing countries have suffered in recent years, not only from poor funding and under-trained staff, but from a lack of up-to-date literature on the subject. This book is the second in a three-volume series on rural extension that aims to address this situation. It contains supplementary information on the cases featured in Volume 1 (see 1552).